Розвиток та становлення сучасної теорії розчинів електролітів - Головко, М. (Праці наукового товариства ім. Шевченка, 2011)
The principal steps of the development and formation of the modern theory of electrolyte solutions are reviewed The Debye-Huckel and Bogolubov theories are discussed. Special attention is given to early papers by Yukhnovskii to their analysis from viewpoint of the present state of theory. The connection of generalization of Debye-Huckel theory with the results of the mean spherical approximation is presented. The role of plasma parameter and cluster expansions in the formulation of non-mean field approximations is shown . The statistical -mechanical methods of the description of the effects of ionic solvation and ionic association in modern theory of electrolyte solutions is discussed.